Silenced rivers: The ecology and politics of large dams by Patrick McCully - Campbell, Malene (Acta Structilia, 1998)
In his book Patrick McCully asks the question whether the construction of large dams actually do stimulate development in underdeveloped areas. He comes to the same conclusion as Jane Jacobs (1994: 110) and Peter Hall (1988: 163), namely that those projects rather have a detrimental effect on regional development than otherwise. One of the best examples according to him is the so called Tennessee Valley Authority project in the USA.